Applicability of Oral Fluid and Dried Blood Spot for Hepatitis B Virus Diagnosis - Livia Melo Villar; Cristianne Sousa Bezerra; Helena Medina Cruz; Moyra Machado Portilho; Geane Lopes Flores (Canadian Journal of Gastroenterology and Hepatology)
Hepatitis B virus (HBV) is one of the major causes of chronic liver disease worldwide; however most of individuals are not aware about the infection. Oral fluid and dried blood spot (DBS) samples may be an alternative to serum to HBV diagnosis to increase the access to diagnosis in remote areas or high-risk groups. The main objective of this review is to give an insight about the usefulness of oral fluid and DBS for detecting HBV markers. Several groups have evaluated the detection of HBsAg, anti-HBc, and anti-HBs markers in oral fluid and DBS samples demonstrating 13 to 100% of sensitivity and specificity according different groups, sample collectors, and diagnosis assays. In the same way, HBV DNA detection using oral fluid and DBS samples demonstrate different values of sensitivity according type of collection, studied group, extraction, and detection methods. Thus, serological and molecular diagnostic tests demonstrated good performance for detecting HBV using oral fluid and DBS according some characteristics and could be useful to increase the access to the diagnosis of HBV.